2022
DOI: 10.3390/molecules27238475
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol Ameliorates Fibrosis in Rheumatoid Arthritis-Associated Interstitial Lung Disease via the Autophagy–Lysosome Pathway

Abstract: Interstitial lung disease associated with rheumatoid arthritis (RA-ILD) can lead to interstitial fibrosis and even lung failure as a complication of rheumatoid arthritis (RA), and there is currently no effective treatment and related basic research. Studies have found that resveratrol (Res) can improve the progression of RA by regulating autophagy, and increasing evidence supports the connection between autophagy and common interstitial lung disease (ILD). We explored changes in autophagy levels in fibrotic lu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…aqueous ethanolic extract (30:70) showed potential to reduce paw volume/diameter and PGE2, COX-2, IL-1β, IL-6, NF-κB, and TNF-α levels and enhance IL-4 and IL-10 contents in Sprague Dawley rats with induced RA [229]. Additionally, 80 mg/kg daily of chebulanin for 3 weeks significantly suppressed the progression and development of RA in a collagen-induced arthritis mouse model by decreasing the arthritis severity score, attenuating paw swelling and joint destruction, and reducing IL-6 and TNF-α amounts, excised phosphorylated (p)-p38 and p-p65, phosphorylated-c-JUN N-terminal kinase, and phosphorylated NF-κB inhibitor alpha, but without effects on extracellular-signal-regulated kinase levels [231].…”
Section: In Vivo Studiesmentioning
confidence: 96%
See 2 more Smart Citations
“…aqueous ethanolic extract (30:70) showed potential to reduce paw volume/diameter and PGE2, COX-2, IL-1β, IL-6, NF-κB, and TNF-α levels and enhance IL-4 and IL-10 contents in Sprague Dawley rats with induced RA [229]. Additionally, 80 mg/kg daily of chebulanin for 3 weeks significantly suppressed the progression and development of RA in a collagen-induced arthritis mouse model by decreasing the arthritis severity score, attenuating paw swelling and joint destruction, and reducing IL-6 and TNF-α amounts, excised phosphorylated (p)-p38 and p-p65, phosphorylated-c-JUN N-terminal kinase, and phosphorylated NF-κB inhibitor alpha, but without effects on extracellular-signal-regulated kinase levels [231].…”
Section: In Vivo Studiesmentioning
confidence: 96%
“…Hydrogen peroxide is also released, owing to the activation of nuclear factor kappa-lightchain-enhancer of activated B cells (NF-κB) kinases and oxidation, hence stopping reactive species accumulation [228,229]. However, although inflammatory processes are directly linked to individual development, when these responses are exaggerated, carbohydrate damage, lipid peroxidation protein, and nucleic acid oxidation happen, contributing to the onset of many disorders, including AR [230][231][232]. Once again, given that phenolics can counteract oxidative stress and normalize immune responses, it is not surprising that phenolics are a target of extensive research.…”
Section: Anti-inflammatory Abilitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, autophagy plays a significant role in the development of pulmonary fibrosis [18][19][20]. Research has demonstrated that resveratrol can suppress fibrosis in RA-ILD by reinstating autophagy [21].…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, the autophagy process and the nucleotide-binding domain and leucine-rich repeat protein 3 inflammasome activities are inhibited, and the production of pro-inflammatory factors is reduced, thus improving lung inflammation and fibrosis ( Ding et al, 2019 ). In addition, in the fusion process of autophagosome and lysosome, RSV can relieve their inhibitory state and reverse the destruction of autophagosome—lysosome fusion, thus improving ILD ( Bao et al, 2022 ). These findings suggest that RSV can be used as a potential treatment for ILD ( Figure 1 ).…”
Section: Introductionmentioning
confidence: 99%